Amentoflavone Inhibits ERK-modulated Tumor Progression in Hepatocellular Carcinoma In Vitro - LEE, KUN-CHING (In Vivo, 2018)
Background/Aim: A previous study indicated that amentoflavone inhibits tumor growth of breast cancer. However, the anti-cancer effects and mechanism of amentoflavone in hepatocellular carcinoma (HCC) have not been elucidated. The aim of the present study was to verify the effect of amentoflavone on tumor progression in HCC. Materials and Methods: HCC SK-Hep1 cells were treated with different concentrations of amentoflavone or 10 μM PD98059 (extracellular signal-regulated kinases (ERK) inhibitor) for 48 h, respectively, and then cell viability, NF-ĸB activation, levels of tumor progression-associated proteins, and cell invasion were evaluated with 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), NF-ĸB reporter gene assay, western blotting, and cell invasion assay. Results: The results demonstrated that both amentoflavone and PD98059 not only significantly reduced cell viability, NF-ĸB activation, and cell invasion, but also inhibited the expression of tumor progression-associated proteins. In addition, we found that amentoflavone suppresses ERK phosphorylation. Conclusion: The results of the present study suggest that amentoflavone down-regulates ERK-modulated tumor progression in HCC.